A wavelength-preserving all-optical 3r regenerator - J. Slovak; C. Bornholdt; B. Sartorius (Communications - Scientific letters of the University of Zilina, 2004)
A novel all-optical 3R regenerator operated in the optically clocked scheme (OC-3R) is presented. The regenerator basically comprises two semiconductor components: an ultra-long semiconductor optical amplifier (UL-SOA) for effective use of fast nonlinearities and a self-pulsating PhaseCOMB-laser for all-optical clock recovery. The dynamic behaviour of the key devices is investigated theoretically and experimentally. An excellent regenerative performance of the assembled OC-3R is demonstrated by eye analysis and by bit error rate (BER) measurements at 40 Gbit/s.